Sago Forest Density Analysis Using Vegetation Index Transformation (Case Study in Tawiri Village, Teluk Ambon District, Ambon City) - Kezia E Lewantaur; Wilem A Siahaya; Elisa J Gazpersz (Agrologia, 2022)
Ecologically, sago palms can grow, develop and produce on marginal land where other plants are difficult to grow. The research was conducted in a sago forest in Tawiri Village, Teluk Ambon District, Ambon City, Maluku Province. The purpose of the study was to map the density level of sago forest in Tawiri Village at 2016 based on the transformation of the vegetation index on the Landsat imagery. The method used in the research was Normalized Difference Vegetation Index (NDVI) transformation Landsat-7 ETM+. The results showed that there were three levels of sago forest density: a medium density level of 13.3%, a low density of 3.4%, and a high density of 1.6% of the research area. In the study area, non-sago area covered 81% of the research area. The accuracy of the  sago forest density analysis at 2016 was 92%, which means there was a similarity between the image classification and the actual situation in the field.